Morpho-Semantic Analysis of Word Formation in Abraham Lincoln’s “The Gettysburg Address” - Yulius Yosef Kasimo; Yuliana M. D' Karmel Kara (General English Education, 2026)
This research analyzes word formation, including inflection, derivation, grammatical meaning, lexical meaning, contextual meaning. This research employed a qualitative approach supported by morphological and semantic theory. The study focuses on Abraham Lincoln's "Gettysburg Address" delivered in 1863. Data collected analyzes words related to inflection and derivation. It has been identified that a number of inflectional morphemes show the presence of morphemes marked by the suffixes "-s", "-d", "-ed", "-ing", "-er", "-al-" and "-re". Six derivational morphemes found in the speech sample include: -ment, -ion, un-, -ing, -ly, and -ed or -d. Inflected and derivative words exhibit a high degree of semantic interconnectedness, both in terms of their lexical meanings and the contexts in which they are employed. Abraham Lincoln sought to emphasize five key points: Change catalysts are historical, and national philosophy is crucial. Respect those who built America's foundation. Unity and dedication are crucial to fulfilling past revolutionaries' unrealized ideals. This research enhanced the understanding of morphological features and semantic categories while reinforcing the non-negotiable importance of human rights and the indispensable role of a democratic system of government. Future research may compare morpho-semantic patterns in political speeches using corpus-based or critical discourse analysis to examine persuasive functions.